2008
DOI: 10.1021/es800741u
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Examination of the Protonation Behavior of Fulvic Acids Using Differential Absorbance Spectroscopy

Abstract: The effects of pH changes on the absorbance spectra of fulvic acids, which constitute a major part of natural organic matter (NOM) were examined based primarily on the example of standard Suwannee River fulvic acid (SRFA). Differential absorbance spectra of SRFA generated at varying pH values were determined to be rich in features that are absent in the conventional spectra. Analysis of the differential absorbance revealed the existence of two predominant types of pH-active chromophores which produced features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 28 publications
10
103
0
1
Order By: Relevance
“…Comparing measured spectra with reference spectra is the general idea of differential spectra and discloses features that are unrevealed in whole spectra (Dryer et al, 2008). In our study, component 2 from PMF can be understood as average ATR-FTIR spectrum of all Fe-OM coprecipitates from either Ah-derived or Ap-derived effluent.…”
Section: Om Composition In the Fe-om Co-precipitatesmentioning
confidence: 82%
“…Comparing measured spectra with reference spectra is the general idea of differential spectra and discloses features that are unrevealed in whole spectra (Dryer et al, 2008). In our study, component 2 from PMF can be understood as average ATR-FTIR spectrum of all Fe-OM coprecipitates from either Ah-derived or Ap-derived effluent.…”
Section: Om Composition In the Fe-om Co-precipitatesmentioning
confidence: 82%
“…A fluorescence analysis of model compounds has demonstrated that electron-donating functional groups (e.g., amine, hydroxyl) can also significantly increase fluorescence intensities [2]. It has been well recognized that carboxylic chromophores overwhelmingly contributed to the changes in fluorescence at pH values between 3.0 and 5.0, whereas phenolic chromophores are predominant at pH values between 8.0 and 10.0 [38].…”
Section: Eem Spectra Deconvoluted By Parafac Analysismentioning
confidence: 99%
“…Optical titrations of lower concentration samples have been used to successfully model proton binding in Suwannee River Fulvic Acid (SRFA) by the use of pH dependent differential absorbance (A) (Dryer et al, 2008). The NICA-Donnan model describes two distributions of titratable groups centered at pH 4 and pH 7-8 respectively (Koopal et al 2005;De Wit et al 1993a;De Wit et al 1993b).…”
Section: Introductionmentioning
confidence: 99%
“…A direct comparison of divergent sources of fulvic and humic acid model compounds including an aquatic terrestrially derived fulvic acid, Suwannee River fulvic Acid (SRFA) and a microbial source of fulvic acid, Pony Lake fulvic Acid (PLFA) (Brown et al, 2004;McKnight et al, 1994), the soil derived humic acids Elliott humic acid (EHA) and Leonardite humic acid (LHA) and a terrestrially derived aquatic humic acid Suwannee River humic acid (SRHA) ( Table 1). Analysis and comparison of untreated and borohydride reduced model humic compounds particularly at short wavelength (< 350) using potentiometric and optical titrations, spectral slope values (S), difference plots (A) (Dryer et al, 2008), fluorescence emission spectra, (Jørgensen et al, 2011), and fluorescence difference spectra (F) (Del Vecchio & Blough, 2004) provide insight into how electronic interactions work universally in the environment as well as how differences that exist between sources humic materials can potentially augment existing knowledge about the fate and transport of humic substances in the environment (Hernes & Ronald Benner, 2002).…”
Section: Introductionmentioning
confidence: 99%